Early Diagnosis And Management Of Diaphragmatic Injuries - Abd Al-Salam Aziz M. Al-Khatib; Zaid Maad Ahmed Samem; Saad Fakhri Abdulrahman (Pusat Riset dan Inovasi Nasional, 2024)
This prospective study was conducted at the Department of General Surgery in Tikrit Teaching Hospital from December 2008 to December 2012. It included 73 patients who sustained diaphragmatic injuries, primarily from penetrating injuries such as gunshot wounds and shells (65 patients, 89%), with the remaining patients presenting with blunt trauma (8/73, 11%). The study comprised both male and female patients, with a male-to-female ratio of 3.8:1. The majority of patients were in the 20-29 years age group (43/73, 60%). The left hemidiaphragm was the most commonly injured site in both blunt and penetrating traumas, accounting for 89% (7/8) and 66% (43/65) of cases, respectively. Acute presentation with abdominal pain and concurrent intraabdominal and thoracic injuries was the most commonly encountered clinical scenario (58/73, 74.5%). The spleen was the most frequently injured intraabdominal organ in both blunt and penetrating traumas. Diaphragmatic injury should be suspected in all patients with penetrating injury below the nipple in front and inferior scapular angle in the back, confirmed by chest X-ray showing diagnostic findings such as elevation of the injured hemidiaphragm or obliteration of its contour, and/or a pathognomonic